Jenis Penelitian Tafsir Di Indonesia - Nurlizam (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2018)
Toni John as quoted by Federspiel in the introduction of the Popular Indonesian Literature The Qur’an book states that Indonesian Islamic Thought since the 16th century was very great and produced many articles about Traditional Islamic Sciences. Hamzah Fansuri, Ar-Raniri and Syamsudin from Pasai were important scientists at that time, the latest works written by Ar-Raniri had expanded beyond Sout- heast Asia. This scientific culture was then followed by his students and generations after him to this day. In terms of its writing method, the interpretation of the Koran written by Indonesian Muslim intellectuals varies. Diversity can be seen in terms of language, letter usage, langua- ge style and writing method. The variety of languages used is Dutch, Arabic, Javanese, Malay-Jawi and Indonesian. The diversity of letters is seen from the use of Malay and Latin Arabic letters. In terms of met- hods, some use the tahliliy (analytical) method, maudhu’i (thematic) or a combination of both. This article discusses the study of various types of interpretive research in Indonesia that do not yet fully have connections on many sides. The author views that the type of interpretation in Indonesia can be divided into two forms of classification. First, in terms of writing interpreta- tions which are classified into two things, namely using scientific and non-scientific writing standards. Second, in terms of interpretation re- search, which is divided into three research models, namely: Descripti- ve, explorative and developmental.